Isolation and Characterization of Rhizosphere Bacteria for the Biocontrol of Phomopsis azadirachtae Causing Die-back of Neem - Girish, K. (Journal of Scientific Research, 2025)
In this current investigation, rhizosphere bacteria were isolated from plant’s rhizosphere of Andrographis paniculata. The isolated bacteria were evaluated for antagonistic activity by dual culture method against Phomopsis azadirachtae, the fungus causing die-back of neem. One bacterium (C8) that exhibited excellent inhibition of pathogen was selected and characterized by biochemical tests and molecular methods. The ethyl acetate extract of this bacterium was screened against P. azadirachtae at different concentrations such as 2, 4, 6, 8, 10, 20, 40, 50, 60, 80 and 100 ppm by poisoned-food method. The isolated rhizobacterial strain significantly inhibited P. azadirachtae at 40 ppm concentration. This bacterium could be a potential candidate for the biocontrol of P. azadirachtae as well as for the integrated management strategies against this pathogen.